Alone in the world? Imago Dei from theological anthropology to Christology - Nadia Marais (AOSIS, 2021)
In Princeton theologian Van Huyssteen’s (2006) major interdisciplinary work, Alone in the World? Human Uniqueness in Science and Theology, human uniqueness is rhetorically coupled with human aloneness. A comparison with a contemporary theological anthropology, namely Yale theologian Kelsey’s (2009) Eccentric Existence: A Theological Anthropology, shows an alternative approach to the notion or concept of the imago Dei, namely a theological shift from viewing human beings as image(s) of God, to viewing human beings as images of Christ, or images of the image of God. This contribution responds to the invitation implied in Van Huyssteen’s book title – are we alone in the world? – by exploring some of the rhetorical implications of a Christological interpretation of the imago Dei. One such implication may imply a different answer to Van Huyssteen’s question – are we alone in the world?; not yes, but no. Dietrich Bonhoeffer’s idea of Christ’s promeity illustrates how the rhetorical dynamics behind such a move in response – from yes to no – may potentially look, and that a rearticulation of human uniqueness could have direct consequences for how we imagine our human aloneness in the world.